Therapeutic efficacy and safety of artesunate + amodiaquine and artemether + lumefantrine in treating uncomplicated Plasmodium falciparum malaria in children on the rainy south-east coast of Madagascar - Irinantenaina Judickaëlle; Carn Gwénaëlle; Randriamiarinjatovo Dina Ny Aina Liantsoa; Harimanana Aina Nirina; Razanatsiorimalala Seheno; Ralemary Nicolas; Randriarison Maurice; Razafinjato Celestin; Hotahiene Raphael; Randrianarivelojosia Milijaona (Parasite, 2023)
Malaria is a major public health problem in Madagascar, particularly in coastal areas. We conducted a randomized, controlled, parallel-group study of artemisinin-based combination therapy (ACT) in Mananjary and Farafangana, two localities on the rainy south-east coast of Madagascar, from March to September 2018. The efficacy and safety of artesunate + amodiaquine (ASAQ) and artemether + lumefantrine (AL) were assessed according to the WHO protocol with a 28-day follow-up. Children aged 6 months to 14 years with uncomplicated Plasmodium falciparum malaria were randomized to receive ASAQ or AL for three days (1:1). 347/352 (98.5%) randomized patients reached the study endpoint on day 28. Crude adequate clinical and parasitological response (ACPR) rates were 100% (95% CI: 98.8–100%) in the ASAQ group and 96% (95% CI: 93.1–98.9%) in the AL group (per protocol population). However, the PCR-corrected ACPR rate was 97.7% (95% CI: 95.4–100%) in the AL group. Two cases of recrudescence and three of re-infection were observed. Mild and moderate adverse events, including gastrointestinal and/or nervous disorders, were reported in 11.9% (42/352) of patients. We found that ASAQ and AL were safe and efficacious for treating uncomplicated P. falciparum malaria. They may be used for treatment at health facilities and at the community level, and for mass drug administration campaigns.